Correction of Midface Deficiency in Patient With Crouzon Syndrome by Orthognathic Surgery and Patient Specific Facial Implant: Case Report. Issue 2 (27th March 2022) - Ha, Sung-Ho; Lee, HyunJong; Choi, Jin-Young
Abstract : Abstract: Crouzon syndrome, also known as craniofacial dysostosis, is an autosomal dominant inherited disease characterized by early cranial fusion and consequential craniofacial malformations. In patients with Crouzon syndrome, the growth of the midface is affected due to early fusion of the cranial base, which results in exophthalmos, ocular ptosis, midface deficiency, and maxillary retrognathism. Frontofacial advancement using Le Fort III osteotomy is the conventional method for treating patients with Crouzon syndrome. However, this procedure has drawbacks such as extensive operation field and high possibility of serious complications (eg, meningitis). For patients with mild symptoms, facial esthetics and proper occlusion can be promoted through conventional orthognathic surgery, but midface deficiency cannot be completely resolved. Thus, in this case report, midface augmentation was performed for a patient with Crouzon syndrome by undergoing conventional orthognathic surgery, along with patient-specific implants made using a 3D virtual technique. Implants were 3D printed using polyetherketoneketone and simultaneously implanted during the orthognathic surgery. After the surgery, not only were the patient's occlusion and facial esthetics improved, but also exophthalmos and ocular ptosis were reduced by the midfacial augmentation effect of patient-specific implants placed in the midface. Since the implants were made exactly as what surgeons have intended through computer-aided design (CAD)/computer-aided manufacturing (CAM) and 3D printing techniques, problems such as under-/over-correction were avoided. In addition, the possibility of implant malpositioning was minimized using surgical stents as implants were passively fitted on the patient's bone surface. This case verified that the application of 3D technology to the field of oral and maxillofacial surgery can reduce the invasiveness of surgery and improve the accuracy of the operation. Therefore, by using cutting-edge technologies, the field of oral and maxillofacial surgery is expected to be developed further in the near future.